1928
DOI: 10.5962/bhl.title.7269
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic variation and the rate of growth of bacteria, by Arthur T. Henrici ...

Abstract: reserve material and protected by a more or less resistant membrane. Gonidia and regenerative bodies participate actively in the process of multiplication, whereas the other reproductive organs are in the first place resting forms. Gonidia, regenerative bodies, and probably microcysts are produced by all bacteria, while arthrospores, exo-and endospores are less common; though there are indications that they will be discovered in many more cases, as soon as these problems are more thoroughly investigated (1921,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
88
0

Year Published

1932
1932
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 0 publications
7
88
0
Order By: Relevance
“…The five strains are proposed to comprise a new species of a new genus, Oceanicaulis alexandrii gen. nov., sp. nov., the type strain of which is C116-18 T (=DSM 11625Since the original description of the genus Caulobacter by Henrici & Johnson (1935), stalked bacteria from a wide range of sources, including soils, freshwater and marine environments, have been assigned to the genus, mainly on the basis of their characteristic prosthecate (Anast & Smit, 1988;Stahl et al, 1992). Originally thought to be restricted exclusively to oligotrophic habitats, in the last decade an extensive number of isolates exhibiting heterotrophic traits and relatively versatile metabolisms have been isolated from eutrophic environments, such as secondary waste water treatment facilities (Fenton, 1994;MacRae & Smit, 1991), and assigned to the genus Caulobacter.…”
mentioning
confidence: 99%
“…The five strains are proposed to comprise a new species of a new genus, Oceanicaulis alexandrii gen. nov., sp. nov., the type strain of which is C116-18 T (=DSM 11625Since the original description of the genus Caulobacter by Henrici & Johnson (1935), stalked bacteria from a wide range of sources, including soils, freshwater and marine environments, have been assigned to the genus, mainly on the basis of their characteristic prosthecate (Anast & Smit, 1988;Stahl et al, 1992). Originally thought to be restricted exclusively to oligotrophic habitats, in the last decade an extensive number of isolates exhibiting heterotrophic traits and relatively versatile metabolisms have been isolated from eutrophic environments, such as secondary waste water treatment facilities (Fenton, 1994;MacRae & Smit, 1991), and assigned to the genus Caulobacter.…”
mentioning
confidence: 99%
“…The biological interactions are also important, as indicated by the fact that the blooming pulse of cyanobacteria and diatoms are followed by the increase of bacterial counts, likely due to the supply of organic matters from planktons. 68) Both the temperature dependence and biological interactions in the production and abundance of bacterioplanktons have been confirmed through 8-year monitoring in a hypertrophic lake. 69) By analyzing several bacterial profiles for 80 bacteria isolated from three ponds, Hashizume et al 43) reported marked horizontal variation in the distribution of these bacteria with their seasonal changes.…”
Section: Microbes In Surface Watermentioning
confidence: 90%
“…His report in 1676 marks the discovery of biofilms [9]. However, only in the first half of the twentieth century with the work of Henrici [10] and Zobel [11] was the import of biofilms really appreciated by the scientific community, and finally the word biofilm was first used in 1981 [12], which marks the recognition of its function and organization.…”
Section: Introductionmentioning
confidence: 99%